Метод R-функцій в математичному моделюванні стаціонарних процесів теплопровідності у кусково-однорідних середовищах - Рєзнік, Ю. С. (ХНУРЕ, 2023)
The paper considers the application of the structural method of R-functions to the solution of the problem of mathematical modeling of stationary processes of heat conduction in piecewise homogeneous media. An approach to build such a solution structure of the problem is described, which would accurately take into account both the conditions on the outer boundary of the body and the conjugation condition on the boundary of the medium-environment contact.
Keywords: метод R-функцій; математичне моделювання стаціонарних процесів теплопровідності; кусково-однорідні середовища